Does kernel position on the cob affect zeaxanthin, lutein and total carotenoid contents or quality parameters, in zeaxanthin-biofortified sweet-corn?. (30th March 2019) - Calvo-Brenes, Paula; Fanning, Kent; O'Hare, Tim
Highlights: Kernel position within a cob significantly affect zeaxanthin, lutein and total carotenoid content. Quality parameters are not affected by kernel position. Compared to kernel position, influence of genotype and maturity have a major effect on the evaluated variables. Abstract: Influence of kernel position on zeaxanthin, lutein, total carotenoid (TC) and quality parameters was evaluated in a zeaxanthin-biofortified and a commercial yellow sweet-corn. Cobs were harvested at six different maturity stages, and the above variables in kernels from the tip-end, middle and base of the cobs were analysed. Kernels from the tip-end had highest zeaxanthin and TC in the zeaxanthin biofortified sweet-corn, and highest lutein and TC in the commercial yellow sweet-corn. In both, the highest concentration was followed by kernels from the middle and then basal kernels. Quality parameters were not significantly affected by kernel position. The current trial indicates that, although kernel position within a cob can significantly affect the carotenoid concentration, this effect is minor compared to the influence of genotype and kernel maturity. However, if a threshold zeaxanthin concentration is to be achieved, the positional effect should be taken into consideration as a contributing factor.